Ritual Language as Social Action: A Case Study of Nika Ro Neku in The Digital Space - Asyrafunnisa, Asyrafunnisa; Abbas, Herawaty; Arafah, Burhanuddin (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
The traditional marriage ritual of Nika Ro Neku is one of the cultural heritages of the Bima community that is rich in symbolic, social, and spiritual meaning. In the digital age, this ritual has been documented and disseminated through online media, causing changes in its practice and linguistic structure. Social media, video recordings, and online communication have led to changes in the structure of speech, the roles of participants, and the social meanings contained within. This study aims to analyze the transformation of language and the roles of participants in the ritual using Alessandro Duranti's anthropological linguistic approach, particularly the concepts of indexicality, performance, and participation. The method used is a qualitative descriptive approach based on digital ethnography, with data consisting of speech excerpts from YouTube videos and online interviews. The results show that the performative dimension in ritual speech is the most dominant aspect, where speech not only conveys information but also shapes social realities such as blessings, acceptance, and collective identity. Digital transformation has led to the reinterpretation of social indices, a shift in performativity toward visual content, and the expansion of participants' roles from local communities to a global audience. This study demonstrates that digital documentation does not erase cultural meaning but rather reformulates it within a new media context.